Single Molecule RNA Localization and Translation in the Mammalian Oocyte and Embryo - Jansova, Denisa; Aleshkina, Daria; Jindrova, Anna; Iyyappan, Rajan; An, Qin; Fan, Guoping; Susor, Andrej (Journal of molecular biology, 2021)
During oocyte growth the cell accumulates RNAs to contribute to oocyte and embryo development which progresses with ceased transcription. To investigate the subcellular distribution of specific RNAs and their translation we developed a technique revealing several instances of localized translation with distinctive regulatory implications. We analyzed the localization and expression of candidate non-coding and mRNAs in the mouse oocyte and embryo. Furthermore, we established simultaneous visualization of mRNA and in situ translation events validated with polysomal occupancy. We discovered that translationally dormant and abundant mRNAs CyclinB1 and Mos are localized in the cytoplasm of the fully grown GV oocyte forming cloud-like structures with consequent abundant translation at the center of the MII oocyte. Coupling detection of the localization of specific single mRNA molecules with their translation at the subcellular context is a valuable tool to quantitatively study temporal and spatial translation of specific target mRNAs to understand molecular processes in the developing cell.
Keywords: mRNA; Proto-Oncogene Proteins c-mos; localization; nekódující RNA; cytoplazma; oocyty; In Situ Hybridization, Fluorescence; protoonkogenní proteiny c-mos; Animals; Single Molecule Imaging; polyribozomy; Cyclin B1; imaging; Mice; hybridizace in situ fluorescenční; Polyribosomes; Gene Expression Regulation, Developmental; Female; Protein Biosynthesis; vývojová regulace genové exprese; Cytoplasm; zobrazení jednotlivé molekuly; embryo savčí; cyklin B1; subcellular; ženské pohlaví; RNA, Messenger; zvířata; Embryo, Mammalian; Oocytes; RNA, Untranslated; messenger RNA; proteosyntéza; translation; myši